Reading the Af-Pak Narrative, from the US disengagement to Russian re-engagement - ambrish -- dhaka (Сравнительная политика, 2017)
The US has prolonged its stay in Afghanistan with the security situation remaining far from improving. The indefatigable demand for resources to maintain counter-insurgency operations was a major debate in 2016 US Presidential elections with a demand for an earlier withdrawal from America’s Trillion dollars plus war effort. Russians having sensed the weakening of the US influence warmed upto the idea of new Afghan situation involving Taliban and their masters, the Pakistan army. Russia had experienced vulnerabilities of Islamisation in Central Asia and Caucasus, and the ISIS brand radicalisation added to the fear of political destabilisation of Central Asian states. The Islamic State showed up in Afghanistan and Pakistan as ISIS-Khorasan branch. Russia needed Pakistan as an ally to fight Daesh’s presence on its southern periphery. However, there remained many intertwined security challenges that complicate the South Asian geopolitics, especially, the Af-Pak region. Russia’s Taliban policy might be the hitherto unused leverage that it might be using in order to strike balance all along the shatterbelt.